Analysis of Five-Level DSTATCOM for Harmonic Reduction in Power System Due To Non-Linear Loads - N. Raveendra; V. Madhusudhan; A. Jayalaxmi (Institute of Advanced Engineering and Science, 2016)
This paper deals with the elimination of harmonics at PCC in the presence of non-linear type of loads. Introduction of five-level DSTATCOM at PCC injects compensating currents for the minimization of harmonic content in the source currents. Non-linear loads when connected to the system draw non-linear components of current leaving undesired harmonics at the source side. DSTATCOM when connected to the system at the coupling point induces compensating currents to nullify harmonics. This paper introduces the simulation modelling of five-level DSTATCOM for harmonic elimination. Matlab/Simulink modelling was done for the system without DSTATCOM and its harmonic contents were shown. The system without DSTATCOM is compared with the system with the presence of DSTATCOM showing their respective THD in the source current. Five level DSTATCOM was validated by considering fixed load and variable load. Simulation work was carried out for three types of systems and results were obtained using Matlab/Simulink.